Weight changes, metabolic syndrome and all‐cause mortality among Asian adults living with HIV. Issue 3 (23rd November 2021) - Han, Win Min; Law, Matthew G.; Choi, Jun Yong; Ditangco, Rossana; Kumarasamy, Nagalingeswaran; Chaiwarith, Romanee; Ly, Penh Sun; Khusuwan, Suwimon; Merati, Tuti Parwati; Do, Cuong Duy; Yunihastuti, Evy; Azwa, Iskandar; et al.
Abstract: Objectives: We investigated weight changes following antiretroviral therapy (ART) initiation, the development of metabolic syndrome (MetS) and its association with all‐cause mortality among Asian adults living with HIV. Methods: Participants enrolled in a regional Asian HIV‐infected cohort with weight and height measurements at ART initiation were eligible for inclusion in the analysis. Factors associated with weight changes and incident MetS (according to the International Diabetic Federation (IDF) definition) were analysed using linear mixed models and Cox regression, respectively. Competing‐risk regression models were used to investigate the association of MetS with all‐cause mortality. Results: Among 4931 people living with HIV (PLWH), 66% were male. At ART initiation, the median age was 34 [interquartile range (IQR) 29–41] years, and the median (IQR) weight and body mass index (BMI) were 55 (48–63) kg and 20.5 (18.4–22.9) kg/m 2, respectively. At 1, 2 and 3 years of ART, overall mean (± standard deviation) weight gain was 2.2 (±5.3), 3.0 (±6.2) and 3.7 (±6.5) kg, respectively. Participants with baseline CD4 count ≤ 200 cells/µL [weight difference (diff) = 2.2 kg; 95% confidence interval (CI) 1.9–2.5 kg] and baseline HIV RNA ≥ 100 000 HIV‐1 RNA copies/mL (diff = 0.6 kg; 95% CI 0.2–1.0 kg), and those starting with integrase strand transfer inhibitor (INSTI)‐based ART (diff = 2.1 kg; 95% CI 0.7–3.5 kg vs. nonnucleoside reverse transcriptase inhibitors) had greater weight gain. After exclusion of those with abnormal baseline levels of MetS components, 295/3503 had incident MetS [1.18 (95% CI 1.05–1.32)/100 person‐years (PY)]. The mortality rate was 0.7 (95% CI 0.6–0.8)/100 PY. MetS was not significantly associated with all‐cause mortality in the adjusted model ( P  = 0.236). Conclusions: Weight gain after ART initiation was significantly higher among those initiating ART with lower CD4 count, higher HIV RNA and an INSTI‐based regimen after controlling for baseline BMI. Greater efforts to identify and manage MetS among PLWH are needed.